2018
DOI: 10.1098/rsob.170266
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and regulation of γ-tubulin complexes

Abstract: Microtubules are major constituents of the cytoskeleton in all eukaryotic cells. They are essential for chromosome segregation during cell division, for directional intracellular transport and for building specialized cellular structures such as cilia or flagella. Their assembly has to be controlled spatially and temporally. For this, the cell uses multiprotein complexes containing γ-tubulin. γ-Tubulin has been found in two different types of complexes, γ-tubulin small complexes and γ-tubulin ring complexes. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 72 publications
(133 reference statements)
2
53
0
1
Order By: Relevance
“…In fission yeast, filamentous fungi and metazoans, some GCP2s and GCP3s are replaced in the complex by an additional GCP4, GCP5 and GCP6 proteins and in metazoan γTuRC is a stable complex whose assembly is independent of the recruitment to target structures such as centrosomes (Farache et al, 2018;Lin et al, 2015;Murphy et al, 2001;Oegema et al, 1999;Tovey and Conduit, 2018). The exact stoichiometry and subunit order of human γTuRC is not known.…”
Section: Introductionmentioning
confidence: 99%
“…In fission yeast, filamentous fungi and metazoans, some GCP2s and GCP3s are replaced in the complex by an additional GCP4, GCP5 and GCP6 proteins and in metazoan γTuRC is a stable complex whose assembly is independent of the recruitment to target structures such as centrosomes (Farache et al, 2018;Lin et al, 2015;Murphy et al, 2001;Oegema et al, 1999;Tovey and Conduit, 2018). The exact stoichiometry and subunit order of human γTuRC is not known.…”
Section: Introductionmentioning
confidence: 99%
“…g-tubulin is not required for MT assembly at the fat body ncMTOC g-tubulin, partnering with g-tubulin complex proteins (GCPs) to form the g-tubulin ring complex (g-TuRC), is widely employed as a MT nucleator or anchor at centrosomes and other MTOCs (Kollman et al, 2011;Lin et al, 2015;Oakley et al, 2015;Muroyama and Lechler, 2017; Sanchez and Feldman, 2017;Farache et al, 2018;Sallee et al, 2018;Tillery et al, 2018). Compared to the larval brain, the fat body expresses significantly less g-tubulin, about 120-fold less ( Figure 9A), but is detectable by IF and is localized to the ncMTOC throughout larval developmental stages ( Figure 9C, D), together with other g-TuRC components including GCP2 and GCP3 ( Figure 6).…”
Section: Centrosomal Proteins Are Localized At the Fat Body Ncmtoc Bumentioning
confidence: 99%
“…Compared to the relatively large number of MT plus-end proteins, few MT minus-end proteins have been identified. Gammatubulin (g-tubulin), a conserved and essential MT minus-end protein that nucleates centrosomal MTs (Kollman et al, 2011;Oakley et al, 2015;Farache et al, 2018), also nucleates and anchors non-centrosomal MTs in many differentiated cell types (Chen et al, 2017;Muroyama and Lechler, 2017;Sanchez and Feldman, 2017;Tillery et al, 2018). The XMAP215/Msps/Stu2/ Dis1/Alp14/ZYG-9/ch-TOG/MOR1 is an ancient family of MT polymerases that was recently identified as a new in vivo MT nucleator at centrosomes and spindle pole bodies through its association with g-tubulin (Flor-Parra et al, 2018;Gunzelmann et al, 2018;Thawani et al, 2018); a role for the MT polymerase at nucleating MTs at ncMTOCs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…γ-TuRCs assemble in the cytosol but they are typically inactive until recruited to specific sites, such as microtubule organising centres (MTOCs), the cytosol around mitotic chromatin or the sides of pre-existing microtubules via Augmin/HAUS [18][19][20][21][22] . A range of MTOCs exist, including centrosomes, the Golgi apparatus and the nuclear below the epidermis, making them ideal for imaging through the translucent body wall.…”
Section: Introductionmentioning
confidence: 99%